2016
DOI: 10.23917/jramathedu.v1i1.1791
|View full text |Cite
|
Sign up to set email alerts
|

Improving Teaching Quality and Problem Solving Ability Through Contextual Teaching and Learning in Differential Equations: A Lesson Study Approach

Abstract: Differential equations is a branch of mathematics which is closely related to mathematical modeling that arises in real-world problems. Problem solving ability is an essential component to solve contextual problem of differential equations properly. The purposes of this study are to describe contextual teaching and learning (CTL) model in differential equations course, to improve lecturers’ abilities in implementing CTL, and to improve students’ problem solving ability in differential equations. The study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 9 publications
3
23
0
10
Order By: Relevance
“…Contextual Teaching and Learning based on Lesson Study can help students be more active and also help teachers in the process of designing a learning that is appropriate for students. Contextual Teaching and Learning model based on Lesson Study can be well received by students, shown through a positive response in the application of learning models and the learning atmosphere noted to be dynamic (Khotimah, 2016). Contextual Teaching and Learning model based on Lesson Study can also help students become easier in understanding the learning indicated by the increased learning outcomes in the cognitive domain (Fadillah et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Contextual Teaching and Learning based on Lesson Study can help students be more active and also help teachers in the process of designing a learning that is appropriate for students. Contextual Teaching and Learning model based on Lesson Study can be well received by students, shown through a positive response in the application of learning models and the learning atmosphere noted to be dynamic (Khotimah, 2016). Contextual Teaching and Learning model based on Lesson Study can also help students become easier in understanding the learning indicated by the increased learning outcomes in the cognitive domain (Fadillah et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Boyce & DiPrima (2001), states that DE is an equation in which there are one or several derivatives. DE is one of the advanced mathematical concepts that are widely used in applied mathematics applied in the fields of physics, chemistry, biology, engineering, social and psychology (Boyce & DiPrima, 2001;Machin, Diaz, & Trigo, 2012;Khotimah & Masduki, 2016 ;Vajravelu, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The contextual approach is a strategy that emphasizes the involvement of students in finding their own material or concepts learned and connecting them in real-world situations [11]. The contextual approach is a strategy in learning that has seven principles or components, they are: Constructivism, Inquiry, Questioning, Learning Community, Modeling, Reflection, and Authentic Assessment [12].…”
Section: Introductionmentioning
confidence: 99%